Preliminary SEA of the Great Western Development Strategy : The Five Key Development Domains - World Bank (World Bank, Washington, DC, 2021)
The Strategic Environmental Assessment (SEA) objectives are to provide a general baseline description of the environment in western China, analysis of the environmental impacts of Great Western Development Strategy (GWDS) plans, and to provide suggestions for mitigating measures or alternatives to facilitate the GWDS decision-making process. This study represents a trial-SEA in China and provides an opportunity to develop experience and capacity at the strategic level of assessment, to date this level of analysis (strategic planning) has been especially rare in China. The vast scale, scope and duration of the GWDS make it a challenging subject for a preliminary SEA. The development and implementation of SEA systems represents the most important development in impact assessment over the last decade, yet there remains significant debate on exactly what SEA is and a wide variety of different approaches are currently in use. This is because of the very broad practical implications of SEA, which means that even the most advanced countries are still refining their systems to get the most out of this tool.